Proses Peningkatan dan Hasil Belajar Matematika menggunakan Model Kooperatif Tipe Numberred Head Together (NHT) pada Siswa Kelas 2 SDN No36/Vi Rantau Panjang III - Rodiah; Megawati (Indonesian Journal Publisher, 2024)
Students still find math to be a challenging subject, as indicated by their math learning outcomes.students, a relatively low number. Inadequate learning choices are the cause of poor learning outcomes.approaches. One method to address these issues is to utilize the learning framework that incorporates an active approach.involvement of students in the educational process. One potential model that can encourage active participationIn the cooperative learning model, student roles include Numbered Head Together (NHT). colossal, gigantic beast rampaged through the city, causing chaos and destruction wherever it went.The NHT model supports the presence of member groups with varying levels of ability. This research was conducted. Research was carried out on second-grade students at SDN No36/VI Rantau PanjangIII. The primary factors that should be examined are students' daily outcomes, students' abilities, and students' assessment results. The NHT model is utilized in practice. performed over 2 rounds, with each round comprising 4 stages. The stages include planning and action. observation and contemplation. The outcomes from observations during the second cycle indicated favorable improvements in students. These transformations were observed in students' performance, involvement, opinions, and problem-solving skills. Solving math problems on your own can benefit overall group learning results. The text should not be changed. The math learning scores have gone up to 8214 on average, indicating a high level of proficiency in math. The rate of competence is 86.48%.